2019
DOI: 10.32828/mdj.v14i1.762
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status in relation to nutritional status among kindergarten children aged (4-5) years old in Karbala city / Iraq

Abstract: Back ground: Dental caries and periodontal disease were the most common andwidely spread diseases affecting children. The nutrition may be one of the factorsaffecting the severity of the oral diseases. The Aims of this study was theassessment of the following oral diseases (dental caries, gingivitis) in addition toassessment of oral hygiene among 4-5 years old children in Karbala city –Iraq.Furthermore, nutritional status was assessed in relation to oral diseases.Materials and methods: A sample of 658 children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The parotid glands account for 50% of stimulated saliva secretion and only 20% for unstimulated Saliva. 37 Also, Hashem’s study was of a poor quality allowing a high potential for bias.…”
Section: Discussionmentioning
confidence: 99%
“…The parotid glands account for 50% of stimulated saliva secretion and only 20% for unstimulated Saliva. 37 Also, Hashem’s study was of a poor quality allowing a high potential for bias.…”
Section: Discussionmentioning
confidence: 99%
“…5 Several studies were conducted in Iraq investigating the nutritional status in relation to various variable. [6][7][8][9][10] Few were found that investigated the teeth eruption status. In 2008, Gatta et al clarified that tooth emergence is a process of growth and therefore is related with other body processes, especially child's weight and height.…”
Section: Methodsmentioning
confidence: 99%